Green synthesis of nanoparticles using medicinal plants as an eco-friendly and therapeutic potential approach for neurodegenerative diseases: a comprehensive review - Izadi, Rezvan; Bahramikia, Seifollah; Akbari, Vali (Frontiers in Neuroscience, 2024)
Central nervous system disorders impact over 1.5 billion individuals globally, with neurodegenerative diseases such as Alzheimer’s, Parkinson’s, and Huntington’s diseases being particularly prominent. These conditions, often associated with aging, present debilitating symptoms including memory loss and movement difficulties. The growing incidence of neurological disorders, alongside a scarcity of effective anti-amyloidogenic therapies, highlights an urgent need for innovative treatment methodologies. Nanoparticles (NPs), derived from medicinal plants and characterized by their favorable pharmacological properties and minimal side effects, offer a promising solution. Their inherent attributes allow for successful traversal of the blood–brain barrier (BBB), enabling targeted delivery to the brain and the modulation of specific molecular pathways involved in neurodegeneration. NPs are crucial in managing oxidative stress, apoptosis, and neuroinflammation in ND. This study reviews the efficacy of green-synthesized nanoparticles in conjunction with various medicinal plants for treating neurodegenerative diseases, advocating for further research to refine these formulations for enhanced clinical applicability and improved patient outcomes.